Potential Of Psychoeducation Media Based On The Internet Of Things For The Optimization Of Hypertension Management In The Elderly - Fitriani, Dewi; Handoyo, Lukman; Setiawan, Heri; Ferman Syah, Fery (Jurnal EduHealth, 2023)
Elderly people with hypertension are a group that often do not comply with disease management. Psychosocial problems are one of the variables that contribute greatly to this non-compliance. In the current era of technological development, psychoeducation using Internet of Things-based media can be one of the interventions provided for the elderly. However, the use of this media has never been applied with the principle of being sensitive to changes in the elderly's sensing system, so it is necessary to explore the perceptions and experiences of health service providers for hypertensive elderly in the community. The aim of this research is to explore the perceptions of elderly health service providers in community settings regarding the implementation of education for hypertensive elderly. This research is a qualitative descriptive study involving five participants. Participants came from elements of the NCD Program, the Elderly Program and Community Health Nursing Program Coordinator at the Community Health Center as well as Community Health Workers. Data collection was carried out using the Focus Group Discussion technique and the results were analyzed thematically. The research results showed three themes: 1) Interventions Not Yet Diverse; 2) Limitations of Educational Media; 3) Technology Considerations in Elderly Education/Psychoeducation. Primary health services that create and apply Internet of Things-based psychoeducational media need to pay detailed attention to the principles and content so that they are easy to read and understand by the elderly.